DETECTION OF THE OVULATION TIME VIA HORMONE LEVELS IN THE PERIPHERAL BLOOD OF THE SUBFERTILE WOMEN WITH REGULAR MENSTRUAL CYCLE - Aydin, Turgut; Koroglu, Nadiye; Albayrak, Nazli; Insel, Mert Akin Akin (ELSEVIER SCIENCE INC, 2022)
78th Annual Scientific Congress and Expo of the American-Society-for-Reproductive-Medicine (ASRM), Anaheim, CA, OCT 22-26, 2022